Optimising The Production Of Chiral Alcohol Via Aspergillus Niger Catalysed Biotransformation Of 1-(4-Bromo-Phenyl)-Ethanone - Abas, Fatimatul Zaharah (2011)
Chiral alcohols are useful starting materials for the synthesis of various biologically active compounds. In this study, the biocatalytic reduction of ketone via asymmetric reduction process using Aspergillus niger as a whole-cell biocatalyst was carried out in order to produce (R)-1-(4-bromo-phenyl)-ethanol. From the result obtained in this sudy, it shows that the exponential phase was the best period for biotransformation to take place compared to the stationary phase, since the production rate (0.063 mM/h) at exponential phase was higher than the production rate (0.028 mM/h) at stationary phase. In addition, the optimization study for biotransformation via shake-flask system shows that the optimum condition was found to be at 48th hr incubation time under pH 6.68 and at 31.85oC with the lowest amount of substrate concentration which is 6.78 mM.